Learn ethical hacking from scratch your stepping stone to penetration testing - Sabih, Zaid (Packt Publishing, 2018)
This book is designed to help you learn the basics, it assumes that you have no prior knowledge in hacking, and by the end of it you'll be at a high intermediate level being able launch attacks and hack computer systems just like black-hat hackers do, not only that but you'll also learn how to secure systems from these attacks.